Un premier aperçu de la diversité génétique de cinq microbes eucaryotique de l'océan arctique - Edgar, Robyn (Université Laval, 2015)
Despite their abundance, diversity, importance to primary production and the Arctic marine ecosystem, the genetic diversity of Arctic marine microbial eukaryotes remains relatively unknown. Recent molecular studies have shown that the species thriving in the Arctic are phylogenetically divergent from non-polar species of marine protists. To begin to understand the evolutionary history and genetic diversity of species from the Arctic Ocean, five Arctic microalgae isolates (a pelagophyte, dictyochophyte, chrysophyte, cryptophyte and haptophyte) were grown under a variety of conditions to generate transcriptomes of all five species and a draft genome of the pelagophyte. Analysis of the transcriptomic and genomic data of the pelagophyte revealed the genetic capacity to use organic nitrogen and live under low light conditions, similar to a temperate bloom-forming pelagophyte. A phylogenetic analysis of genes specific to both photosynthetic and non-photosynthetic physiology provided insight into the evolutionary history of the pelagophyte and the other four Arctic marine protists. Malgré leur abondance, leur diversité et leur importance pour la production primaire et l'écosystème marin arctique, la diversité génétique des microbes marins eucaryotes arctiques reste relativement inconnue. De récentes études moléculaires ont montré que les espèces florissantes dans l'Arctique sont phylogénétiquement divergentes des espèces de protistes marins non-polaires. Pour mieux à comprendre l'histoire évolutive et la diversité des espèces dans l'océan Arctique, cinq cultures de microalgues arctiques (un pélagophyte, un dictyochophyte, un chrysophyte, un cryptophyte et un haptophyte) ont été cultivées sous différentes conditions pour générer des transcriptomes de ces cinq espèces et produire une ébauche du génome du pélagophyte. L'analyse des données de transcriptomique et de génomique du pélagophyte ont démontré sa capacité génétique à utiliser l'azote organique et son aptitude à vivre sous de faibles conditions de lumière, de ...